Komposisi Jenis dan Ukuran Glass Eel (Anguilla spp.) di Muara Sungai Konaweha, Kabupaten Konawe, Provinsi Sulawesi Tenggara - Fekri, Latifa; Pangerang, Utama Kurnia; Lawelle, Sjamsu Alam (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2022)
The mouth of the Konaweha River, located in Sampara Village, Kapoila District, Konawe Regency, Southeast Sulawesi Province. These waters are inhabited by eel fish and have great potential in supplying glass eel (eel seeds). This study aims to determine the species composition and size of glass eel in the Konaweha river estuary. Catching glass eels was carried out in May-October 2022 using pocket set net fishing gear. The number of glass eels was found with a total of 1,502 individuals. Identification of the type of glass eel was determined based on the morphometric characters of the percentage value of the ratio of the ano-dorsal length (AD) to the total length (TL) (AD/TL) %. There were two types of glass eels caught during the study, namely Anguilla bicolor Pacifica and Anguilla marmorata. A. marmorata as many as 986 individuals while Anguilla bicolor Pacifica was found as many as 516 individuals. Anguilla marmorata caught with a total length of 46.59-48.92mm and A. bicolor Pacifica 46.00-48.27mm. The highest catch was in July, namely 1,050 individuals. The A. marmorata species dominates the catch every month.